Agile data warehousing project management : business intelligence systems using Scrum - Hughes, Ralph, 1959- (Morgan Kaufmann, 2013)
You have to make sense of enormous amounts of data, and while the notion of "agile data warehousing? might sound tricky, it can yield as much as a 3-to-1 speed advantage while cutting project costs in half. Bring this highly effective technique to your organization with the wisdom of agile data warehousing expert Ralph Hughes. Agile Data Warehousing Project Management will give you a thorough introduction to the method as you would practice it in the project room to build a serious "data mart.? Regardless of where you are today, this step-by-step implementation guide will prep.